IMPACT OF TEMPERATURE CHANGE ON GROWTH OF LABEO ROHITA: DEVELOPMENT OF A GROWTH MODEL - DAS, M. K.; SRIVASTAVA, P. K.; DEY, S.; MONDAL, MD. L.; MUKHOPADHYAY, M. K.; SAHA, P. K. (Journal of the Inland Fisheries Society of India, 2021)
Enhanced temperature is one of the most important drivers of climate change as evidenced by a perceptible rise of air and water temperature in various regions of India. Unit rise in water temperature affect the physiological features of freshwater fish in aquaculture. Investigations were conducted to assess the impact of increasing water temperature of 29 ºC, 30 ºC, 31 ºC, 32 ºC, 33 ºC, 34 ºC and 35 ºC on the growth, Labeo rohita fingerlings reared for five weeks in aquarium. The fishes were fed pelletised feed ad libitum. Fish reared at 34 ºC water temperature exhibited significantly (P<0.05) faster growth (SGR-2.36 % body weight per day) than those reared at other temperatures. The change in growth rates were insignificant between 29 ºC, 30 ºC, 31 ºC and 32 ºC treatment groups but growth rates significantly increased in the temperatures ranging from 32 ºC to 34 ºC and there after it decreased. A linear growth model of L. rohita fingerlings growth has been developed using the data generated. This simple growth model provided a reliable projection of growth (SGR %) with unit rise of temperature within the range of 29 º to 34 ºC. This will help fish culturists to develop adaptation strategies with regard to suitability of fish species and fish culture practices under the climate warming scenarios. Key words: Temperature, Growth, Indian Major Carp, Labeo rohita